Étude de l'effet de la variété sur les propriétés physico-chimiques et microbiologiques des pommes commerciales (Cas des variétés : Red Delicious, Granny Smith et Golden Delicious ) - Bendali, Chaimaa (My University, 2025)
This study was conducted from April 15 to May 18, 2025, in several laboratories, including the Biochemistry and Microbiology Laboratory of the Faculty of Natural and Life Sciences at Abdelhamid Ibn Badis University of Mostaganem. Its objective was to evaluate the physical, chemical, and microbiological characteristics of three apple varieties (Red Delicious, Granny Smith, and Golden Delicious), harvested in April 2025 in the Mostaganem region. Physical analyses focused on the external appearance of the fruits, including size, weight, and shape. Chemical analyses were carried out to quantify the contents of polyphenols, endogenous flavonoids, vitamin C, and the Brix index. In parallel, microbiological tests were performed to identify bacterial and fungal flora present on the samples. The results revealed notable morphological differences between the varieties. Biochemical assays confirmed the presence of antioxidant compounds such as vitamin C, flavonoids, and polyphenols. Finally, microbiological analysis showed contamination of the samples by various species of bacteria and molds.
Keywords: Red Delicious, Granny Smith, Golden Delicious, vitamin C, flavonoids, polyphenols